SARS-CoV-2 infection in meat and poultry workers after the “first wave” (Summer 2020): a cross-sectional study on knowledge, attitudes, practices (KAP) of Italian occupational physicians: SARS-CoV-2 infection in meat and poultry workers - Riccò, Matteo; Baldassarre, Antonio; Ferraro, Pietro; Melodia, Pietro; Stocchi, Manuel; Magnavita, Nicola (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: This cross-sectional study assessed knowledge, attitudes and practices (KAP) of Italian Occupational Physicians (OPs) on Coronavirus disease 2019 (COVID-19) among meat/poultry processing plant workers (MPWs) (Summer season 2020). Methods: Data were collected through an online questionnaire including demographic characteristics, and items about COVID-19-related KAP in MPWs. A logistic regression was modelled in order to characterize explanatory variables of the outcome variable of having any professional experience as OP in meat/poultry processing industry. Results: A total of 424 OPs (mean age 49.0 ± 9.1years; 49.5% males) participated into the survey. Despite a generally good level of knowledge on SARS-CoV-2 pandemic, OPs having professional experience with MPWs failed to recognize any increased risk for COVID-19 (Odds Ratio [OR] 0.162; 95% Confidence intervals [95%CI] 0.039-0.670), and were less likely to recommend periodical tests via nasal swabs (OR 0.168, 95%CI 0.047-0.605). On the contrary, they identified socioeconomic status of MPWs as a risk factor (OR 5.686, 95%CI 1.413-22.881), recommending cleaning interventions on changing rooms and canteens (OR 16.090, 95%CI 1.099-259.244). Conclusions: In conclusion, we reported a diffuse underestimation of the risk for COVID-19, that was alarmingly higher among professionals who should be more familiar with the specific requirements of MPWs. Some significant knowledge gaps were also clearly identified, stressing the opportunity for tailored educative interventions (www.actabiomedica.it)